Functionalized metal-organic frameworks for photocatalytic degradation of organic pollutants in environment. (March 2020) - Zhang, Xi; Wang, Jing; Dong, Xing-Xing; Lv, Yun-Kai
Abstract: Currently, many kinds of organic pollutants in air and water have a negative impact on humans and the environment. Notably, as a type of new functional materials, metal-organic frameworks (MOFs) with well-ordered porous structures and numerous active sites have been proven to be ideal photocatalysts for the degradation of organic pollutants. In the past few years, many encouraging achievements have been made in the research field of MOFs for photocatalysis. And a large number of functionalized MOFs have been constructed to improve photocatalytic activity. In this review, recent progress in the photocatalytic degradation of organic pollutants in both air and water using functionalized MOFs are summarized in detail. The focus is on photocatalytic mechanisms and some strategies employed to achieve higher degradation efficiency. Furthermore, the challenges and outlooks in this promising filed are also discussed. We hope this review would be useful for designing more functionalized MOFs with greater photocatalytic performance for the degradation of organic pollutants in the environment. Graphical abstract: Image 101029 Highlight: The latest progress on photocatalytic degradation of organic pollutants in air and water using functionalized MOFs are reviewed. Some strategies to improve the degradation efficiency are presented. The photocatalytic mechanisms are summarized. The challenges and outlooks of MOFs for photocatalytic degradation of organic pollutants are given.